2014
DOI: 10.5935/1806-0013.20140027
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions in pain

Abstract: BACKGROUND AND OBJECTIVES: Nursing interventions are any care based on nurses' judgment and clinical knowledge, based on a scientifically supported action, carried out and planned for patients' benefit. These are very important to control pain since pain, when inadequately treated, affects the quality of life of patients and caregivers in physical, psychological, social and spiritual dimensions. So, this study aimed at identifying nursing interventions to handle pain and whether they relate to those proposed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
1
Order By: Relevance
“…Nursing itself, in addition to the resources exposed in this study, could have made use of complementary therapies for pain relief interventions, both in the outpatient clinic and in the hospital. Among the complementary therapies that could be used, the following stand out: application of cold or heat, control of the environment (comfort), distraction, teaching (procedure and treatment), stimulation of the imagination, stimulus to coping, massage, music therapy, relaxation, touch therapy and aromatherapy (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing itself, in addition to the resources exposed in this study, could have made use of complementary therapies for pain relief interventions, both in the outpatient clinic and in the hospital. Among the complementary therapies that could be used, the following stand out: application of cold or heat, control of the environment (comfort), distraction, teaching (procedure and treatment), stimulation of the imagination, stimulus to coping, massage, music therapy, relaxation, touch therapy and aromatherapy (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other strategies could minimize the effects of pain, since it can affect quality of life, physical, psychological, social and spiritual dimensions of patients and their caregivers if not treated properly. Thus, non-pharmacological methods for pain relief are increasingly being used (15) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a substantial portion of these patients did not receive any intervention for pain relief. The literature suggests that insufficient knowledge about mechanism of action, half-life, drug-drug interactions, and dosage often leads to undertreatment of pain (16)(17) . Although physicians are responsible for prescribing analgesic agents, pain management per se is performed by the nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of nonpharmacological measures as supporting strategies in the treatment of pain and reduction of opioids is still challenging because of the strong biomedical model adopted in clinical practice and the knowledge gap under construction in recent years. Brazilian studies have shown opportunities and space for nurses to work with pain management in patients at all levels of healthcare and their involvement and skills to manage pain, for example, using integrative practices to manage pain 41,42…”
Section: Introductionmentioning
confidence: 99%